The Effect of Price and Service Quality on Customer Satisfaction of PT Huda Express Courier Services at Mcdonald’s Bintaro Restaurant - Putri Nilam Kencana (Jurnal Ad'ministrare, 2020)
Customer satisfaction is the main aspect that must be met by the company, with the creation of customer satisfaction, demand will also rise. This study aims to determine the effect of price and service quality on customer satisfaction PT. Huda Express at McDonald’s Bintaro Restaurant. The method used is a quantitative method with an associative approach, with 100 respondents. Statistical tests using multiple regression analysis, coefficient of determination, and hypothesis testing with t test and F test. The results of the study, showed that price and service quality have a positive effect on customer satisfaction with the regression equation Y = 2,279 + 0,307X₁ + 0,130X₂. Price contributed 62.5% to customer satisfaction, while service quality contributed 59.6% to customer satisfaction. From testing hypotheses using statistical tests Fcount> F table or (163.410> 3.09), this is also strengthened with a probability of 0,000 <0.05. Thus H0 is rejected and H1 is accepted. This means that there is a positive and significant effect simultaneously between price and quality of service on customer satisfaction.